2016
DOI: 10.1080/14703297.2016.1180257
|View full text |Cite
|
Sign up to set email alerts
|

Participation and collaborative learning in large class sizes: wiki, can you help me?

Abstract: Collaborative learning has a long tradition within higher education. However, its application in classes with a large number of students is complicated, since it is a teaching method that requires a high level of participation from the students and careful monitoring of the process by the educator. This article presents an experience in collaborative learning adapted to large class sizes using wikis. The objective is to check if wikis allow for effective collaborative learning methods to be introduced into lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The peer-review process enables students to refine their comprehension and enhance their ability to analyze, evaluate, and synthesize material (Sadler & Good, 2006). Research additionally shows that peer instruction increases student comprehension and enhances conceptual reasoning and problem solving (Crouch & Mazur, 2001). Peer evaluations also engage learners in the assessment process, leading to better academic performance and achievement of course learning outcomes (Asikainen et al, 2014;.…”
Section: Sources Of Student Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…The peer-review process enables students to refine their comprehension and enhance their ability to analyze, evaluate, and synthesize material (Sadler & Good, 2006). Research additionally shows that peer instruction increases student comprehension and enhances conceptual reasoning and problem solving (Crouch & Mazur, 2001). Peer evaluations also engage learners in the assessment process, leading to better academic performance and achievement of course learning outcomes (Asikainen et al, 2014;.…”
Section: Sources Of Student Feedbackmentioning
confidence: 99%
“…Concurrently, an abundant body of research has demonstrated the benefits of experiential learning, including increased student engagement and improved student learning outcomes (e.g., Brooks & Simpson, 2014; Hamer, 2000). Only recently has a small and limited research stream merged these topics to address the adoption of experiential learning methods in large-format classes (Broadbent et al, 2018; de Arriba, 2017; Eichler & Peeples, 2016; Hancock, 2010; Lund Dean & Wright, 2017). In an effort to address some key concerns of employing experiential learning methods in large classes, we propose a framework utilizing multisource feedback to improve the link between student experience and learning/development.…”
mentioning
confidence: 99%
“…While there are no easy answers to these challenges, in such circumstances faculty need to be creative in how they engage students to think critically about issues beyond profitability. For example, one study found that the use of wikis can facilitate collaborative learning and active student involvement (de Arriba, 2017).…”
Section: Escaping Misinformation: Paving a Road Toward The Recovery Omentioning
confidence: 99%
“…A number of approaches have been used to mitigate the negative consequences of being a member of a large class. This includes discussions of the pedagogical benefits and assessment of IT (de Arriba, 2017; Maringe & Sing, 2014; Mtshali, Maistry, & Govender, 2015; Saunders & Hutt, 2015; Schaffer, Young, Ligon, & Chapman, 2017), MOOCs (Maringe & Sing, 2014), lecture capture (Freeman, 1998; Owston, Lupshenyuk, & Wideman, 2011), supplementary media (Saunders & Hutt, 2015), student-response systems (Hancock, 2010; Heaslip, Donovan, & Cullen, 2014; Mayer et al, 2009; Patterson, Kilpatrick, & Woebkenberg, 2010), peer-teaching and peer-assessment (Asikainen et al, 2014), and flipped classrooms (Eichler & Peeples, 2016). However, much of the evaluation of such programs is conducted from the perspective of the provider and few include detailed qualitative accounts that explore the nuances of how the mode of assessment has affected the learner and the experience of learning (Cullen & Turnbull, 2005).…”
Section: Overviewmentioning
confidence: 99%